2022
DOI: 10.1001/jamanetworkopen.2022.0595
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cancer Among Patients With Pediatric-Onset Inflammatory Bowel Disease

Abstract: IMPORTANCEBecause the incidence of pediatric-onset inflammatory bowel disease (IBD) is increasing, knowledge of the long-term risk of cancer in this patient population is required. OBJECTIVE To evaluate the relative rate of cancer among patients with pediatric-onset IBD. DATA SOURCES A comprehensive systematic search was performed of MEDLINE and Embase from the date of database inception to October 31, 2021. STUDY SELECTION All unselected, population-based cohort studies of pediatric-onset IBD assessing the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…About 25% of all IBD diagnoses present before adulthood [ 3 ]. Compared to adults, childhood-onset IBD has been linked to a more severe disease course, e.g., cancer [ 4 ], growth failure [ 5 , 6 ], and a negative impact on school performance and health-related quality of life [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 25% of all IBD diagnoses present before adulthood [ 3 ]. Compared to adults, childhood-onset IBD has been linked to a more severe disease course, e.g., cancer [ 4 ], growth failure [ 5 , 6 ], and a negative impact on school performance and health-related quality of life [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, colorectal cancer (CAC) has been reported as a long-term complication of chronic inflammation associated with inflammatory bowel disease [2][3][4]. Correspondingly, evidence has suggested that adults with inflammatory bowel disease are at higher risk for CAC than are healthy individuals, with children showing a 2.4-fold greater risk [5].…”
Section: Introductionmentioning
confidence: 99%
“…Children who are diagnosed with inflammatory bowel disease (IBD) are more than twice as likely to develop cancer in comparison with the general pediatric population according to new research. The findings were published in JAMA Network Open 1 …”
mentioning
confidence: 99%